Early mobilization post-myocardial infarction: A scoping review. - Haroon Munir; Jake Fromowitz; Michael Goldfarb (PLoS ONE)
Bedrest and immobilization following a myocardial infarction (MI) can lead to functional impairment that can persist following hospitalization. Early mobilization (EM) is associated with good functional and clinical outcomes in critical care, medical and surgical settings. However, the impact and current role of EM in post-MI care has not been well-defined. Our objective was to assess the evidence for post-MI mobilization, define current post-MI mobilization practice, and understand perspectives of cardiovascular professionals toward mobilization. A scoping review related to "early mobilization" and "myocardial infarction" was performed using the Joanna Briggs Institute Methodology. Pubmed, Embase, Google Scholar, Cochrane Library and CINAHL databases were included. Results were categorized into six topic areas. There were 59 references included in the analysis. There was evidence for the effectiveness and safety of earlier mobilization in experimental studies of the pre-revascularization era, but there was a lack of strong evidence for EM in contemporary post-MI care. Mobilization appears to be safe following arterial catheterization and is associated with minimal hemodynamic and respiratory compromise. Most people are delayed in mobilizing post-MI and spend the majority of the initial hospitalization period lying in bed. Only 1 of 7 current major cardiovascular professional societies guidelines recommend EM post-MI. There were no studies exploring the perspectives of cardiovascular professionals toward mobilization. EM may be beneficial in the post-MI care. However, there is an evidence gap for the impact of EM post-MI in the contemporary literature. More robust evidence from randomized clinical trials is required to inform clinicians and influence practice.